The Iron-containing Catalysts in the Petrochemical Processes - G.D. Zakumbaeva; B.T. Tuktin; A.D. Gazizova; A.I. Lyashenko (Eurasian Chemico-Technological Journal, 2002)
The iron-containing catalysts modified by zeolites, copper, nickel and other additives have been studied in the process of hydrorefining of butylmercaptan (C4H9SH) -alkane (C5H12, C6H14 or C10H22) mixture and of the real gasoline and diesel oil fractions. It has been shown that the iron-containing modified catalysts posses the multi-functional properties. The processes of hydrodesulfurisation, hydroisomerization and hydrocracking run in parallel over these catalysts. The catalysts studied show the high hydrodesulfurisation activity. Conversion of butylmercaptan over these catalysts is about 100% at 400 В°C, P = 3.5 MPa and H2/feed = 250/1. It has been established, that the conversion of butylmercaptan in model mixes over KTZ-13 is decreased with increase of molecular weight of hydrocarbons in the following order: C5H12 > C6H14 > C10H22. After hydrorefining, hydroisomerization and hydrocracking of the real diesel fraction the temperature of freezing of the final product is decreased by 9.7-17.1 В°C. Introduction of zeolites (HY, HZSM and clinoptilolite) in composition of the iron-containing catalysts allowed to increase the adsorptive properties of catalysts concerning to hydrogen and oil products. The big pore diameter facilitates the transport of the reactant molecules into pores and of the reaction products from pores.